Evaluation of anti-bacterial activity of novel 2, 3-diaminoquinoxaline derivatives: design, synthesis, biological screening, and molecular modeling studies. Issue 1 (31st December 2022) - Suthar, Suresh Kumar; Chundawat, Narendra Singh; Pal Singh, Girdhar; M. Padrón, José; Payghan, Pavan V.; Jhala, Yuvraj Kunwar
ABSTRACT: A series of nonsymmetrical 2, 3-diaminoquinoxaline derivatives prepared straight-forwardly by the C-N coupling between chloro-quinoxaline (2, 3-DCQ) and various amino substrates. Synthesized products (4a-z) with excellent purity ( 1 HNMR) without performing flash column chromatography purification. Investigated the antibacterial activity of selected nine compounds against Gram-positive, Gram-negative bacterial strains, and additional fungal strains. Overall, the selected screened compounds (4b, 4c, 4 h, and 4 n) presented significant antibacterial activity against bacterial strains. The resulting lead, displaying a novel quinoxaline compound (4c), showed antibacterial activity between 10.5 and 14.89 mm against all strains except A. Niger. Molecular docking studies revealed the binding poses and critical interactions of 2, 3-diaminoquinoxaline analogues at the quinolone-binding site of S. aureus DNA gyrase. The docking results are in accordance with the antimicrobial testing data. Binding of these new analogues (as DNA intercalators) at quinolone-binding site involves the contribution from: I) Protein: Ser-1084, II) DNA: DG (G) 9 and DA (H) 13; and III) Mg +2 ion for their binding.